Endoscopic Papillary Large Balloon Dilation Reduces the Need for Mechanical Lithotripsy in Patients with Large Bile Duct Stones: A Systematic Review and Meta-Analysis. (6th March 2014) - Madhoun, Mohammad F.; Wani, Sachin; Hong, Sam; Tierney, William M.; Maple, John T.
Abstract : Background . Removal of large stones can be challenging and frequently requires the use of mechanical lithotripsy (ML). Endoscopic papillary large balloon dilation (EPLBD) following endoscopic sphincterotomy (ES) is a technique that appears to be safe and effective. However, data comparing ES + EPLBD with ES alone have not conclusively shown superiority of either technique. Objective . To assess comparative efficacies and rate of adverse events of these methods. Method . Studies were identified by searching nine medical databases for reports published between 1994 and 2013, using a reproducible search strategy. Only studies comparing ES and ES + EPLBD with regard to large bile duct stone extraction were included. Pooling was conducted by both fixed-effects and random-effects models. Risk ratio (RR) estimates with 95% confidence interval (CI) were calculated. Results . Seven studies (involving 902 patients) met the inclusion criteria; 3 of 7 studies were prospective trials. Of the 902 patients, 463 were in the ES + EPLBD group, whereas 439 underwent ES alone. There were no differences noted between the groups with regard to overall stone clearance (98% versus 95%, RR = 1.01 [0.97, 1.05];P = 0.60 ) and stone clearance at the 1st session (87% versus 79%, RR = 1.11 [0.98, 1.25];P = 0.11 ). ES + EPLBD was associated with a reduced need for ML compared to ES alone (15% versus 32%; RR = 0.49 [0.32, 0.74];P = 0.0008 ) and was also associated with a reduction in the overall rate of adverse events (11% versus 18%; RR = 0.58 [0.41, 0.81];P = 0.001 ). Conclusions . ES + EPLBD has similar efficacy to ES alone while significantly reducing the need for ML. Further, ES + EPLBD appears to be safe, with a lower rate of adverse events than traditional ES. ES + EPLBD should be considered as a first-line technique in the management of large bile duct stones.